ABRAHAMIC PEACE THEOLOGY IN ISRAEL-IRAN CONFLICT RESOLUTION: A CROSS-RELIGIOUS PERSPECTIVE - Pauzian, Muhamad Hilmi (Religi: Jurnal Studi Agama-agama, 2025)
The escalating Israeli-Iranian conflict in 2025 has become a complex geopolitical crisis that has a significant impact on global stability, while conventional approaches based on politics, economics, and security have not succeeded in producing sustainable solutions. This study aims to analyze the potential contribution of Abrahamic peace theology in providing a theoretical and practical framework for defusing the Israeli-Iranian conflict through the identification of universal values in the Jewish, Christian, and Islamic traditions as the foundation of interfaith dialogue and long-term peace efforts. The research method uses a comparative theological analysis with a qualitative-descriptive approach to the primary texts of the three Abrahamic traditions (Tanakh, Talmud, Bible, Quran, Hadith) and secondary literature from theologians and scholars of interfaith studies. The results of the study identified three universal values as common ground: justice (tzedek, dikaiosyne, 'adl), compassion (hesed, agape, mercy), and peace (shalom, eirene, salam), and found the principles of pikuach nefesh (Jewish) and maslaha (Islam) as theologically valid moral foundations for constructive dialogue. The three-stage applicative model—recognition, dialogue, and reconciliation—has been successfully formulated as a practical framework for conflict resolution. This study concludes that Abrahamic peace theology can be a normative and practical alternative in international diplomacy by providing a spiritual and moral dimension as the foundation for sustainable peace, while also making a new contribution to academic discourse on the role of religion in contemporary geopolitical conflict resolution. Keywords: Theology of Abrahamic Peace; Interfaith Dialogue; Universal Values; Conflict Resolution; Reconciliation   Konflik Israel-Iran yang semakin meningkat pada tahun 2025 telah menjadi krisis geopolitik yang kompleks dan berdampak signifikan terhadap stabilitas global, sementara pendekatan konvensional yang berbasis politik, ekonomi, dan keamanan belum berhasil menghasilkan solusi yang berkelanjutan. Penelitian ini bertujuan untuk menganalisis potensi kontribusi teologi perdamaian Abrahamik dalam menyediakan kerangka teoretis dan praktis untuk meredakan konflik Israel-Iran melalui identifikasi nilai-nilai universal dalam tradisi Yahudi, Kristen, dan Islam sebagai fondasi dialog antaragama dan upaya perdamaian jangka panjang. Metode penelitian ini menggunakan analisis teologi komparatif dengan pendekatan kualitatif-deskriptif terhadap teks-teks utama dari tiga tradisi Abrahamik Tanakh, Talmud, Alkitab, Al-Quran, Hadits dan literatur sekunder dari para teolog dan cendekiawan studi antaragama. Hasil penelitian mengidentifikasi tiga nilai universal sebagai landasan bersama: keadilan (tzedek, dikaiosyne, 'adl), welas asih (hesed, agape, belas kasih), dan perdamaian (shalom, eirene, salam), serta menemukan prinsip-prinsip pikuach nefesh (Yahudi) dan maslaha (Islam) sebagai landasan moral yang valid secara teologis untuk dialog yang konstruktif. Model aplikatif tiga tahap—pengakuan, dialog, dan rekonsiliasi—telah berhasil dirumuskan sebagai kerangka kerja praktis untuk resolusi konflik. Penelitian ini menyimpulkan bahwa teologi perdamaian Abrahamik dapat menjadi alternatif normatif dan praktis dalam diplomasi internasional dengan menyediakan dimensi spiritual dan moral sebagai landasan bagi perdamaian berkelanjutan, sekaligus memberikan kontribusi baru bagi wacana akademis tentang peran agama dalam resolusi konflik geopolitik kontemporer. Kata Kunci: Teologi Perdamaian Abrahamik; Dialog Antaragama; Nilai-Nilai Universal; Resolusi Konflik; Rekonsiliasi